Design of the Magnetic Resonance Imaging Evaluation of Mineralocorticoid Receptor Antagonism in Diabetic Atherosclerosis (MAGMA) Trial. Issue 9 (26th May 2017) - Rajagopalan, Sanjay; Alaiti, M. Amer; Broadwater, Kylene; Goud, Aditya; Gaztanaga, Juan; Connelly, Kim; Fares, Anas; Shirazian, Shayan; Kreatsoulas, Catherine; Farkouh, Michael; Dobre, Mirela; Fink, Jeffrey C.; et al.
Abstract : Mineralocorticoid receptor (MR) activation plays an essential role in promoting inflammation, fibrosis, and target organ damage. Currently, no studies are investigating MR antagonism in patients with type 2 diabetes mellitus (T2DM) with chronic kidney disease, at high risk for cardiovascular complications, who are otherwise not candidates for MR antagonism by virtue of heart failure. Further, there is limited information on candidate therapies that may demonstrate differential benefit from this therapy. We hypothesized that MR antagonism may provide additional protection from atherosclerosis progression in higher‐risk patients who otherwise may not be candidates for such a therapeutic approach. In this double‐blind, randomized, placebo‐controlled trial, subjects with T2DM with chronic kidney disease (≥ stage 3) will be randomized in a 1:1 manner to placebo or spironolactone (12.5 mg with eventual escalation to 25 mg daily over a 4‐week period). The co‐primary efficacy endpoint will be percentage change in total atheroma volume in thoracic aorta and left ventricular mass at 52 weeks in patients treated with spironolactone vs placebo. Secondary outcomes include 24‐hour mean systolic blood pressure, central aortic blood pressure, and insulin resistance (HOMA‐IR) at 6 weeks. A novel measure in the study will be changes in candidate miRNAs that regulate expression of NR3C2 (MR gene) as well as measuring monocyte/macrophage polarization in response to therapy with spironolactone. We envision that our strategy of simultaneously probing the effects of a drug combined with analysis of mechanisms of action and predictive response will likely provide key information with which to design event‐based trials.